Genotype heterogeneity of high-risk human papillomavirus infection in Ethiopia - Seyoum, Ayichew; Seyoum, Berhanu; Gure, Tadesse; Alemu, Addisu; Belachew, Anteneh; Abeje, Dessalegn; Aseffa, Abraham; Howe, Rawleigh; Mulu, Andargachew; Mihret, Adane (Frontiers in Microbiology, 2023)
Cervical cancer is a vaccine-preventable sexually transmitted disease. In the year 2020, there were an estimated 604,000 new cases and 342,000 deaths worldwide. Although its incidence is global, it is much higher in sub-Saharan African countries. In Ethiopia, there is a scarcity of data about the prevalence of high-risk HPV infection and its association with cytological profiles. Therefore, this study was conducted to fill this information gap. A hospital-based cross-sectional study was conducted from April 26 to August 28, 2021, and enrolled 901 sexually active women. Socio-demographic and other relevant bio-behavioral and clinical data were collected using a standardized questionnaire. Visual inspection with acetic acid [VIA] was done as an initial screening method for cervical cancer. The cervical swab was then collected using L-Shaped FLOQSwabs in eNAT nucleic acid preservation and transportation medium. A Pap test was done to determine the cytological profile. Nucleic acid was extracted using STARMag 96 ProPrep Kit on SEEPREP32. A Real-time multiplex assay was performed to amplify and detect the HPV L1 gene used for genotyping. The data were entered into Epi data version 3.1 software and exported to STATA version 14 for analysis. A total of 901 (age range from 30 to 60 years, mean age = 34.8 years, and SD± 5.8) women were screened for cervical cancer using VIA and 832 women had a valid co-testing (Pap test and HPV DNA testing) results for further process. The overall prevalence of hr HPV infection was 13.1%. Out of 832 women, 88% of them had normal and 12% had abnormal Pap test results. The proportion of high risk HPV was significantly higher among women with abnormal cytology (X2 = 688.446, p < 0.001) and younger age (X2 = 15.3408, p = 0.018). Among 110 women with hr HPV, 14 genotypes (HPV-16, -18, -31, -33, -35, -39, -45, -51, -52, -56, -58, -59, -66, and -68) were identified while HPV-16, -31, -52, -58, and -35 genotypes were highly prevalent. The high risk HPV infection continues to be a significant public health problem among women 30–35 years old. The presence of high-risk HPV irrespective of genotypes is highly correlated with cervical cell abnormalities. Genotype heterogeneity is observed suggesting the importance of periodic geospatial genotyping surveillance for vaccine effectiveness.